Helicobacter pylori infection in the 21st century: Epidemiology, transmission and clinical aspects - Breckan, Ragnar K. (UiT The Arctic University of Norway, 2016)
The papers of this thesis is not available in Munin. Paper I: Breckan, R.K., Paulssen, E.J., Asfeldt, A.M., Mortensen, L., Straume. B., Florholmen, J.: "The impact of body mass index and H. pylori infection on gastro-oesophageal reflux symptoms: A population-based study in Northern Norway." Available in Scand J Gastroenterol 2009(10):1-7. Paper II: Breckan, R.K., Asfeldt, A.M., Straume, B., Florholmen, J., Paulssen, E.J. "Prevalence, comorbidity, and risk factors for functional bowel symptoms: a population-based survey in Northern Norway." Available in Scand J Gastroenterol 2012(47): 1274-82. Paper III: Breckan, R.K., Paulssen, E.J., Asfeldt, A.M., Kvamme, J.M., Mortensen, L., Straume, B., Florholmen, J.: "The all-age prevalence of H. pylori infection and potential transmission routes in a population-based study." (Manuscript). Published version available in: Helicobacter 2015 Background: More than half the world’s population is colonized with Helicobacter pylori (H. pylori) in the gastric mucosa which is the major cause of chronic gastritis and peptic ulcer. Moreover, H. pylori has been associated with the development of non-cardia gastric cancer, the second leading cause of cancer-related deaths worldwide, and has been linked to extra-intestinal diseases, with unsettled causal relationships. The human host immune response is unable to clear the H. pylori infection, and the clinical phenotype is dependent on the interactions between the host immune response and the pathogenicity of the bacterium. The prevalence of H. pylori infection is greatly reduced in developed countries but can be as high as >90% in underdeveloped countries, and remains a great health problem world-wide. Aims In a population based study from two North Norwegian cohorts, we aimed to - describe the association between H. pylori infection and reflux disease, functional bowel symptoms and obesity - describe the all age prevalence of H. pylori - describe potential transmission routes of H. pylori Results: We found that H. pylori is ...